2004
DOI: 10.1002/ejic.200300694
|View full text |Cite
|
Sign up to set email alerts
|

Methacrylate‐Substituted Titanium‐Yttrium Mixed‐Metal Oxo Clusters

Abstract: Upon reaction of titanium propoxide and yttrium 2-methoxyethoxide with a sevenfold excess of methacrylic acid, three different mixed-metal clusters were obtained, depending on the titanium to yttrium alkoxide ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…[8] ). As we have already pointed out in a related case, [9] the simultaneous action of carboxylic acids as hydrogen donors and hydrogen acceptors may stabilize unusual bonding situations.…”
Section: Preparation and Structures Of New Zr12 Clustersmentioning
confidence: 89%
See 1 more Smart Citation
“…[8] ). As we have already pointed out in a related case, [9] the simultaneous action of carboxylic acids as hydrogen donors and hydrogen acceptors may stabilize unusual bonding situations.…”
Section: Preparation and Structures Of New Zr12 Clustersmentioning
confidence: 89%
“…The spectra are in agreement with the molecular symmetries obtained from the solid-state structures. Second, exchange experiments showed that both Zr 6 O 4 (OH) 4 9 ] 2 (6) was treated with a large excess of propionic acid or directly from Zr(OBu) 4 and propionic acid. In either case, the cluster symmetry is retained upon ligand exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them have actually been described as intermediates in various types of polymerization reactions induced by yttrium and lanthanide alkoxides catalysts [6]. Various Ti-Y mixed-metal species such as for instance Ti 4 Y 2 (l 3 -O) 4 (l,g 2 -OMc) 12 (g 1 -OMc) 2 L 2 (L = OHC 2 H 4 OMe or McOH) was reported recently as the result of the addition of a sevenfold excess of methacrylic acid (McOH) to a mixture of Ti propoxide and Y methoxyethoxide in 1:2 stoichiometry [7].We have previously shown that the reaction between yttrium nitrate and the sodium salt of allylacetatoacetate MeCOCH 2 COOCH 2 CH@CH 2 (HAAA) afforded a nonanuclear oxohydroxide species [Y 9 O 2 (OH) 8 (l,g 2 -AAA) 8 (g 2 -AAA) 8 ] À but its moderate solubility [8] led us to consider other yttrium species as alternatives for doping. b-Diketoesters such as 2-(methacryloyloxy)ethyl acetatoacetate (HAAEMA) and especially HAAA were found to modify only slightly the properties of the initial, non-doped microcellular materials [3b,9] and were thus selected as possible 1387-7003/$ -see front matter Ó…”
mentioning
confidence: 99%
“…Most of them have actually been described as intermediates in various types of polymerization reactions induced by yttrium and lanthanide alkoxides catalysts [6]. Various Ti-Y mixed-metal species such as for instance Ti 4 Y 2 (l 3 -O) 4 (l,g 2 -OMc) 12 (g 1 -OMc) 2 L 2 (L = OHC 2 H 4 OMe or McOH) was reported recently as the result of the addition of a sevenfold excess of methacrylic acid (McOH) to a mixture of Ti propoxide and Y methoxyethoxide in 1:2 stoichiometry [7].…”
mentioning
confidence: 99%
“…13) [38]. When the radius is small (Ln = Y [39], Sm, Eu, Gd, Ho, c.n. 8; 1.015-1.08 Å ), the structures of the obtained oxo clusters Ti 4 Ln 2 O 4 (OMc) 14 (HOMc) 2 (Fig.…”
Section: Mixed-metal Oxo Clustersmentioning
confidence: 99%